Interactive Effect of Plant Density and Nitrogen Level on Growth and Yield of Sesame under Irrigation in Northern Sudan - El Mahadi , Abd El Rahman A.; . Ahmed, Faisal E (University of Khartoum Journal of Agricultural Sciences, 2023)
The interactive effect of plant density and nitrogen fertilizer levels on growth and yield of sesame (Sesamum indicum L. cv. Shuak) was investigated under irrigation. The field experiments were conducted during 2005/06 and 2006/07 seasons in the Experimental Farm of the Faculty of Agriculture at Darmali, Nile Valley University, River Nile State, Sudan. Four plant densities (100 000, 150 000, 200 000 and 250 000 plants/ha) and three levels of nitrogen fertilizer (0, 22 and 44 kg N/ha) were used. A split-plot design with four replications was used to execute the experiment. The plants were sown during the first week of July. The results showed that plant height, number of branches per plant, height to first capsule and leaf area index were significantly affected by plant density and level of nitrogen fertilizer. The highest values of these characters were obtained with a plant density of 250 000 plants/ha and treatment receiving 44 kg N/ha. Increasing plant density significantly decreased the number of capsules per plant, seed yield per plant and increased seed yield per unit area. Nitrogen levels significantly increased seed yield and number of capsules per plant. Significant interaction was noted, and the highest seed yield was obtained by the application of 44 kg N/ha at a planting density of 150 000 plants/ha